Comparative study of physicochemical properties and bioactivity of Hericium erinaceus polysaccharides at different solvent extractions. (1st August 2018) - Yan, Jing-Kun; Ding, Zhi-Chao; Gao, Xianli; Wang, Yao-Yao; Yang, Yan; Wu, Di; Zhang, He-Nan
Highlights: Four different solvents were used to extract Hericium erinaceus polysaccharides (HEPs). Extraction solvents had significant effects on physicochemical properties of HEPs. HEP-C extracted with citric acid showed stronger bioactivities than HEP-W and HEP-S. Citric acid can be used in food processing and for the extraction of bioactive PSs. Abstract: In this study, hot water, 0.9% NaCl, citric acid, and 1.25 M NaOH/0.05% NaBH4 were separately used for the extraction of water-soluble H . erinaceus polysaccharides (HEPs; HEP-W, HEP-S, HEP-C, and HEP-A) from the fruit body of Hericium erinaceus . The physicochemical properties and biological activities were then investigated and compared. Results showed that the extraction solvents exhibited significant effects on the extraction yields, molecular weights, monosaccharide compositions, preliminary structural characteristics, microstructures of HEPs and on their contents, such as neutral sugar, uronic acid, protein, and β-(1 → 3)-glucan. In vitro antioxidant activity assays indicated that HEP-C extracted with citric acid solution showed stronger scavenging abilities on hydroxyl and DPPH radicals and antioxidant capacities than HEP-W and HEP-S. Moreover, HEP-C exhibited the strongest inhibitory effects on α-glycosidase and α-amylase activities. Therefore, HEP-C extracted with citric acid can be developed as a potential bioactive ingredient for applications in food, medicine, and cosmetics industries.